World War I : the definitive visual guide from Sarajevo to Versailles - Grant, R. G. (London, United Kingdom : Dorling Kindersley Limited, 2014)
This is the definitive visual history of the people, politics and events of World War I. World War I: The Definitive Visual Guide is a fascinating portrait of a world at war, vividly portraying the conflicts of the Great War on land, sea and in the skies. This history book will tell you everything you ever wanted to know about the First World War. You will uncover the details of the Great War's titanic battles such as Gallipoli, the Somme and Verdun that left an indelible mark on the collective memories of countries and that claimed a generation of young men. You can discover how local fears and hatreds escalated into one vast conflict that was fought out to the bitter end. You can find out about key battles, political and economic forces, individual leaders and technological advances that influenced the course of the First World War. Timelines show you the war unfolding across countries, providing an overview of developments in all the theatres of war. Packed with images, maps, portraits, key artefacts and unforgettable first person accounts, World War I: The Definitive Visual Guide is an uniquely accessible military history of one of the world's most devastating conflicts.
1. The troubled continent, 1870-1914 -- 2. Not over by Christmas, 1914 -- 3. Stalemate, 1915 -- 4. Year of battles, 1916 -- 5. Revolution and disillusion, 1917 -- 6. Victory and defeat, 1918 -- 7. Aftermath, 1919-1923.
Includes index.
Keywords: PICTORIAL WORKS